Efek metode mnemonik pada retensi siswa dan hasil belajar: Materi tentang sistem klasifikasi biologis - Nisa Dhania Atimi; Afandi Afandi; Andi Besse Tenriawaru (Universitas Negeri Jakarta, 2023)
The mnemonic method is one of the procedures that is considered effective for improving students’ learning outcomes and memory. This study aims to examine the effectiveness of the mnemonics methods in improving students' retention and learning outcomes in Biology class on the System of Biological Classifications. The pre-experimental method with one group of pre-test and post-test design was applied in this study. Thirty students of a secondary school in Pontianak were used as research samples taken by using intact group random sampling. The learning outcomes test used was 20 multiple-choice questions with four options having a validity level of 0.86 and a reliability of 0.87. Based on the data analysis, it was concluded: (1) the average learning outcomes before treatment was 48.50 and after treatment was 72.50; (2) the differences in the average student learning outcomes before treatment was = 48.50 and after treatment was = 72.50 (t = 5.517, p <0.05); (3) the level of increase in retention power after treatment of R = 0.85.06% is high. It is recommended that Science-Biology teachers apply mnemonics in a varied and sustainable manner to make it more useful and according to the content of the teaching material to be taught.